ʺTheoretical aspects of professional competence development of mastersoligophrenoeducators in the system of professional trainingʺ - Kapustina О. (Problems of Engineer-Pedagogical Education, 2024)
The article actualizes the problem of developing the professional competence of masters of oligophrenic educators in the system of professional training. Attention is focused on the increased attention of the state to the issue of equal access to knowledge of children with special educational needs, which leads to an increased role of specialists in the field of special education. As a result, there are changes in the educational paradigm and improvements in regulatory and legal support. Based on the results of the analysis of scientific and pedagogical literature, it was found that the problem of developing the professional competence of master's students in the system of professional training is insufficiently developed. The works of scientists highlight certain aspects of this problem: competence and its structure, the role of educational components in the development of general competence, the process of forming professional competence, the leading characteristics of professional competence, the features of professional competence, the development of a special educator, the training of future special education specialists for inclusive education of children with special educational needs. The article also substantiates the importance of general and professional competence in the development of professional competence of master oligophrenic teachers. The author emphasizes that mastering general competence and professional competence is the basis for the development of professional competence, and therefore professional training in higher education should be aimed at their development in master's students. The author concludes that the development of professional competence is based on the study of basic educational components, the mastery of which allows master's students to gain knowledge of the basics of pedagogical science. The role of studying special methods is emphasized, which occurs through the acquisition of special knowledge necessary for professional activity. The prospect of further research is to clarify the essence and structure of the professional competence of master oligophrenic educators in the system of professional training.